A Note on "A Constant-Utility Index of the Cost of Living" - Geary, R. C. (Review of Economic Studies, 1950)
Journal Article A Note on “A Constant-Utility Index of the Cost of Living” Get access R. C. Geary R. C. Geary Dublin Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 18, Issue 1, 1950, Pages 65–66, https://doi.org/10.2307/2296107 Published: 01 January 1950